Entre dobras: um estudo da primeira fase da poesia de Roberto Piva - Silva, Mateus Soares Rodrigues da (2023)
The research entitled Between folds: a study of the first phase of Roberto Piva's poetry (2023) intends to discuss the author's poetics in his first works from the 60s. The poems from this period still require better stylistic appreciation as they repeatedly come being mistakenly associated with the marginal poetry of the 70s and radically different from the literary paradigm that still persisted in the decade in which they were published: Concretism. To do this, it is necessary to scrutinize the critical aporias of this period, as well as present what resources the poet has at his disposal in his creative process, which presents itself as an object of study with the texts of Ode to Fernando Pessoa (1961), the manifestos gathered under the titles Those who saw the carcass (1962), Paranoia (1963) and Piazzas (1964). The devices specific to his poetics make him a singularity within the ontology woven between artists whose aesthetic devices were little or not yet related to the author, that is, until then they had little been explored by the canon of literary criticism and its greatest poets. These first works present a range of poetic references that were not widespread in the 60s, ranging from French Symbolism and Surrealism to the modernist poets Jorge de Lima and Murilo Mendes, authors whose critical fortunes did not yet have the same scope as other renowned authors, as well as references completely unknown in Brazil until then, such as the generation of American beat poets. In this poetics, poets like Dante Alighieri and Garcia Lorca, and painters like Giorgio Di Chirico become aesthetic figures and reveal the operation of a thought carried out with these (and many other) artists, as proposed by Gilles Deleuze's thought-language-action, philosopher whose works mostly make up the theoretical framework used in carrying out this work